Travail social, psychiatrie et alcoolisme dans les années 1950 au prisme des dossiers d’une consultation parisienne - Anatole Le Bras (Astérion)
Drawing on the records of an “alcoholism counselling service” launched in the 13th arrondissement of Paris in 1954, this article studies how social work became part of the new scope of psychiatric care for alcohol addiction, at a time when new medical cures were becoming available. The content and structure of patient records, which we analyse in comparison with papers from medical and social work journals, provide an insight into the day-to-day tasks of the social workers, who worked as closely as possible with alcoholic patients and their families. The article shows that the action of the social worker, which became central, although subordinated to that of psychiatric medicine, took on a psychotherapeutic dimension and was characterised by the need to gain the patient’s trust and ensure their adherence to treatment, thus marking a clear inflection in the relationship with beneficiaries. However, social work was still characterised by its constitutive ambiguity; its control and surveillance functions created difficulties, misunderstandings and disputes with the patients and their relatives.